Mimosa Pudica: experiment of mechanical stimulation of plant movements - Chia, Kelvin Kai Xiang (2015)
Mimosa pudica is a very common plant found in many tropical countries, and is best known for its reaction to touch by closing its leaves. Due to this feature which is rather unique in the plant kingdom, many researches and experiments have been carried out to understand and hypothesize on its mechanism during the stimulation. With this understanding, applications could be brought over into the bioengineering field in which natural movement could be made without physical muscles. During the course of the literature review process, many interesting studies were performed with regards to the Mimosa pudica, but this report would uncover trends of the plant which was not previously identified. The aim of this report is to grasp a better understanding of this unique plant by studying its response to mechanical stimulation, particularly to continuous stimulation. Analyzing this behavior in Mimosa pudica would help to understand the effects of fatigue on the plant’s movement. Another breakthrough experiment was conducted to analyze the force needed to stimulate the leaves of the Mimosa pudica to close. This would put a numerical value to the question of how sensitive the plant actually is. The results concluded that fatigue response differs for the home grown and wild specimens in which home grown specimens show a longer closing and reopening time after each consecutive stimulation, whereas the wild specimens show a faster reopening time. Therefore it is hypothesized that due to conditions the wild specimens undergo day to day, it is more resistant to fatigue as compared to their home grown counterparts. Experimental force data shows that it takes approximately 0.5 to 1 Newton to stimulate the leaves to close. This is a very small amount of force which is expected as even light shaking of the plant by wind could cause the leaves to close.